133 The Potential for Maternal Nutrition to Influence, Health, Development and Subsequent Lifetime Performance of the Pig. (8th October 2021) - Vigors, Stafford; Sweeney, Torres; O'Doherty, John
Abstract: The global population is continuing to grow at a rapid rate leading to increased need for meat and milk products. The pig industry will need to adapt and expand to meet this demand. Improving the productivity of the pig industry is therefore vital in ensuring sustainable growth in the future. The use of dietary additives is a means to improve this animal productivity, however, the most appropriate time to provide dietary additives to ensure maximum benefit with the lowest cost is an area that warrants further exploration. The early-life period is a vital time of physiological, transcriptional, and microbial changes that have a stark impact on lifetime productivity. This early lifetime point provides an opportunity to aid development and impart lifetime alterations and improve animal productivity and health. These changes can be applied by dietary and management interventions to the pig itself or to the dam. The dam is a key influence on the development of the progeny as the primary site of microbial inoculation and is therefore, an interesting target for dietary intervention. With increased legislative and environmental constraints through the ban on antibiotics and the phasing out of zinc-oxide in the EU, there is a need to identify viable natural alternatives to increase productivity particularly in the post weaning period. A wealth of chemodiversity exists in nature in plants and animals developing protective molecules to survive in varying complex biosystems. Our research has established the potential of feeding naturally sustainable bioactives to improve animal performance and health. This talk will explore the strategy of feeding these natural bioactives to the dam to improve lifetime performance of the progeny.